Virtual mitochondrion: towards an integrated model of oxidative phosphorylation complexes and beyond. (24th September 2010) - Mazat, Jean-Pierre; Fromentin, Jonathan; Heiske, Margit; Nazaret, Christine; Ransac, Stéphane
Abstract : The modelling of OXPHOS (oxidative phosphorylation) in order to integrate all kinetic and thermodynamic aspects of chemiosmotic theory has a long history. We briefly review this history and show how new ways of modelling are required to integrate a local model of the individual respiratory complexes into a global model of OXPHOS and, beyond that, into a reliable overall model of central metabolism.